The Dynamic of Intimacy in Prostitution - I Kadek Wahyu Pujhana; Made Diah Lestari (Buletin Psikologi, 2021)
The study of prostitution in Indonesia is dominated by economic, legal, social and health studies. Psychological studies related to the dynamics of intimacy are still limited and mostly conducted in the context of sexual and reproductive health, namely the use of condoms. Intimacy in this article refers to closeness, attachment, and comfort that are psychologically important for prostitutes to manage in order to maintain a personal relationship with clients. The purpose of this article is to describe intimacy in the world of prostitution. Through literature studies and by limiting the study on female prostitutes, this article discusses the definition of prostitution, its history in Indonesia, the role of intimacy in prostitution, the boundaries of intimate relationships, and the link between intimacy and condom use. Two discourses, intimacy as part of sexual relations and intimacy as a form of embeddedness in an economic context are used to understand the boundary line between intimacy as a commercial relationship and intimacy as a non-commercial relationship. This article is expected to contribute to the psychological, legal, and health aspects of prostitution.